(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes data on experimentally selected samples of agricultural products in an infrared drying apparatus, as well as on the drying of samples in an infrared drying apparatus. Some technical and qualitative characteristics of the device are analyzed.